Peran Kompetensi Dalam Memediasi Seleksi dan Pelatihan Terhadap Kinerja Karyawan Pada Pabrik Sadex (Shuttlecock) Nganjuk - Ananda, Alvania Arianti Feby; Suwarsono, Bambang; Kusumawardani, Mawar Ratih (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The current development of human resources has a huge influence on the company. Business competition is currently very competitive and entrepreneurs who run micro and macro businesses must be more able to develop and compete competitively. This research aims to determine the role of competency (Z) in mediating selection (XI) and training (X2) on employee performance (Y) at the Nganjuk Sadex (Shuttlecock) factory. Using a quantitative approach, the research subjects were employees of the Nganjuk Sadex (Shuttlecock) factory. The employee sample consisted of 80 production employees. The sampling technique is saturated sampling. The research uses the Smart-PLS method. The results show that; (1) selection has a significant effect on competency, (2) training has an insignificant effect on competency, (3) selection has an insignificant effect on employee performance, (4) training has a significant effect on performance, (5) competency has a significant effect on employee performance, (6) competence mediating selection has a significant effect on employee performance, and (7) competence mediating training has a significant effect on employee performance.